Model of the hardness prediction for the diffusion nitriding - Horák, Vladimír. (2013)
The plasma nitriding process produces a hard near-surface thin layer of the nitrided material. The thickness of the diffused layer, produced in the course of this process, is between 0.001 and 0.6 mm. The paper presents a diffusion model of plasma nitriding that allows one to predict the material hardness distribution within the near-surface layer as a function of time for a modified nitrogen diffusion coefficient. The temperature dependence of the diffusion coefficient are considered in the paper. Hence, the model involves the reaction rates of nitrides formation. The one-dimensional transient diffusion model is then applied to a thin nitride layer. The solution thus obtained is compared with experimental data for a decrease of hardness as a function of depth and time, until the core hardness is reached.